Immune Thrombocytopenia following COVID-19 Vaccine. (25th June 2022) - Prasad, Sonal; Jariwal, Roopam; Adebayo, Moujidin; Jaka, Sara; Petersen, Greti; Cobos, Everardo
Abstract : Several vaccines have been developed and are being administered against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Common side effects include fever, chills, headache, myalgia, and soreness at the injection site. However, some rare adverse effects have also been reported. We present a case of induced thrombocytopenia presenting with petechiae and mucosal bleeding which developed as an adverse response after first-dose administration of the Moderna COVID-19 vaccine.